Large-scale preventive chemotherapy for the control of helminth infection in Western Pacific countries: six years later. - Antonio Montresor; Dai Tran Cong; Mouth Sinuon; Reiko Tsuyuoka; Chitsavang Chanthavisouk; Hanne Strandgaard; Raman Velayudhan; Corinne M Capuano; Tuan Le Anh; Ah S Tee Dató (Public Library of Science (PLoS), 2008)
In 2001, Urbani and Palmer published a review of the epidemiological situation of helminthiases in the countries of the Western Pacific Region of the World Health Organization indicating the control needs in the region. Six years after this inspiring article, large-scale preventive chemotherapy for the control of helminthiasis has scaled up dramatically in the region. This paper analyzes the most recent published and unpublished country information on large-scale preventive chemotherapy and summarizes the progress made since 2000. Almost 39 million treatments were provided in 2006 in the region for the control of helminthiasis: nearly 14 million for the control of lymphatic filariasis, more than 22 million for the control of soil-transmitted helminthiasis, and over 2 million for the control of schistosomiasis. In general, control of these helminthiases is progressing well in the Mekong countries and Pacific Islands. In China, despite harboring the majority of the helminth infections of the region, the control activities have not reached the level of coverage of countries with much more limited financial resources. The control of food-borne trematodes is still limited, but pilot activities have been initiated in China, Lao People's Democratic Republic, and Vietnam.